2013
DOI: 10.3168/jds.2012-6461
|View full text |Cite
|
Sign up to set email alerts
|

Randomized noninferiority clinical trial evaluating 3 commercial dry cow mastitis preparations: I. Quarter-level outcomes

Abstract: The study objective was to compare the efficacy of 3 commercial dry cow mastitis formulations regarding quarter-level prevalence of intramammary infections (IMI) postcalving, cure of preexisting infections over the dry period, prevention of new infections during the dry period, and risk for a clinical mastitis case between calving and 100d in milk (DIM). A total of 1,091 cows (4,364 quarters) from 6 commercial dairy herds in 4 different states (California, Iowa, Minnesota, and Wisconsin) were enrolled and rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
57
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 26 publications
21
57
2
1
Order By: Relevance
“…The FDA-approved dosing regimen is 1 tube containing 500 mg ceftiofur Check treatment information and milk and meat withdrawal times with drug manufacturer before prescribing based on this information. 42,44,45,[47][48][49][53][54][55][57][58][59][78][79][80][81][82][83] into each affected quarter at the time of dry off, no later than 30 days before calving. 43 Spectramast DC was approved for use in 2005, and thus the few studies that include ceftiofur hydrochloride as a treatment are more current and may be more generalizable to modern dairy farms in North America.…”
Section: Ceftiofur Hydrochloridementioning
confidence: 99%
See 1 more Smart Citation
“…The FDA-approved dosing regimen is 1 tube containing 500 mg ceftiofur Check treatment information and milk and meat withdrawal times with drug manufacturer before prescribing based on this information. 42,44,45,[47][48][49][53][54][55][57][58][59][78][79][80][81][82][83] into each affected quarter at the time of dry off, no later than 30 days before calving. 43 Spectramast DC was approved for use in 2005, and thus the few studies that include ceftiofur hydrochloride as a treatment are more current and may be more generalizable to modern dairy farms in North America.…”
Section: Ceftiofur Hydrochloridementioning
confidence: 99%
“…The most recent study conducted by Arruda and colleagues reported a cure risk of 89% and a new IMI risk of 14.1%. 42 Some of the available studies compared blanket ADCT to selective ADCT with this formulation, which may provide some insight into expected cure rates but does not allow calculation of NNT. The NNT calculated (2.1) for the 1 negative controlled study would only apply to minor pathogens, including coagulase-negative staphylococci and C bovis.…”
Section: Procaine Penicillin G and Dihydrostreptomycinmentioning
confidence: 99%
“…All this foregoing discussion indicates that use of DCT either as preventive or curative measure downsized the incidence of mastitis. Further the antibiotic used in the study has been reported to be comparatively more efficient (Pinedo et al, 2012;Arruda et al, 2013) for prevention and control of udder infection. The decreased incidence of clinical mastitis in DCT group might be due to elimination of infections from udder during the dry period, and higher incidence of clinical mastitis in untreated group may be due to some cows acted as a reservoir of pathogen for re-infection in subsequent lactation (Schukken et al, 2003).…”
Section: Results and Discussion Incidence Of Clinical Mastitismentioning
confidence: 91%
“…Further Scherpenzeel et al (2014) reported 1.7 times higher incidence of clinical mastitis at quarter level in cows dried off without antibiotic than control. Previous studies reported lower incidence of clinical mastitis (3-6% at quarter level and 10.1-14.2% at cow level) during early lactation in dairy cows treated with DCT (Godden et al, 2003;Gundelach et al, 2011;Arruda et al, 2013;Johnson et al, 2016). Further, meta-analysis study on dry cow therapy indicated that quarters infused with DCT have higher cure risk and lower new IMI risk over the dry period than untreated quarters (Halasa et al, 2009).…”
Section: Results and Discussion Incidence Of Clinical Mastitismentioning
confidence: 95%
“…Mammary quarters were considered to have an intramammary infection (IMI) when quarter milk samples showed isolation of significant bacterial colony numbers as described by ARRUDA et al (2013), with slight modification. Since we plated 0.1 mL of milk, we considered presence of IMI as detection of any pathogen at any level, similar to what was described by DOHOO et al (2011).…”
Section: Subclinical Mastitis Definitionmentioning
confidence: 99%